PEMETAAN POTENSI LIKUIFAKSI WILAYAH PESISIR BERDASARKAN DATA CONE PENETRATION TEST DI KELURAHAN LEMPUING, KOTA BENGKULU - Rena Misliniyati; Mawardi Mawardi; Besperi Besperi; Makmun R. Razali; Redho Muktadir (Inersia: Jurnal Teknik Sipil, 2019)
Bengkulu city is one of the cities on the west coast of Sumatra island particularly vulnerable to earthquakes because it is located in an active seismic lines . This vulnerability allows the phenomenon of liquefaction when an earthquake occurs . One of the areas in Bengkulu city which through the lines is Lempuing Village . This study aims to analyze the liquefaction potential based on the data of Cone Penetration Test (CPT) using deterministic methods published by Idriss and Boulanger in 2008 . The data describes soil parameters, collected from the 6 point spread CPT test in Lempuing. Shear wave velocity data obtained from the correlation vs. the CPT data . Seismic load parameters used were obtained from the Indonesian Earthquake Hazard Map of 2010 and the seismic history of the city of Bengkulu. The magnitude of potential liquefaction happens to the value of Safety Factor (SF). The analysis at a depth of 0-2meter showed that most of the area in Lempuing with high potential of liquefaction, indicated by the value of SF is less than 1 . Furthermore , the results of the analysis are  displayed in the form of Liquefaction Potential Map . This map shows that the entire area of Lempuing be in an unsafe condition to the danger of liquefaction during an earthquake with a magnitude > 7.9 earthquake and bedrock acceleration of 0.4 g.